Effect of share price informativeness on share repurchases and share price efficiency - Chee, Chong Meng (2020)
There are two contemporary concerns related to firms repurchasing their shares; (i) share repurchases destroy shareholders’ wealth; (ii) share repurchases manipulate share prices. In light of the first issue, this study also took the further step of examining the information content which is signalled during firms’ share repurchases. By using the concept of share price informativeness (SPI), to provide a better understanding of the influence of SPI on post-repurchase share performance, (i) the effect of stock price informativeness is presented on firms’ share buyback performance; (ii) the level of share repurchase intensity causes share price delay. This study also uses actual share repurchase data to overcome the weaknesses of share repurchase announcement data to provide a more reliable result. Panel regression was employed to analyse two separate samples comprising; 339 US and 180 Malaysia firms who repurchased shares in an 8-year panel dataset between 2012 and 2019. For both the US and Malaysia samples, the firm-specific return variation, which is an SPI measure, was found to have a positive influence on post-repurchase abnormal returns among firms repurchasing their shares. The finding was robust regarding the positive influence of SPI on post-repurchase cost savings. A significantly negative impact of the level of share repurchase intensity was found on share price delay for both US and Malaysia firms repurchasing their shares. The finding remained robust when the ratio of repurchased shares to trading volume was used. These results conclude that share repurchases are good for shareholders’ wealth and promote a more efficient stock price.